CLASH: precise new constraints on the mass profile of Abell 2261 - Coe, Dan; Carrasco, Mauricio; Bartelmann, Matthias (Arxiv, 2012)
We precisely constrain the inner mass profile of Abell 2261 (z=0.225) for the first time and determine this cluster is not "over-concentrated" as found previously, implying a formation time in agreement with ΛCDM expectations. These results are based on strong lensing analyses of new 16-band HST imaging obtained as part of the Cluster Lensing and Supernova survey with Hubble (CLASH). Combining this with revised weak lensing analyses of Subaru wide field imaging with 5-band Subaru + KPNO photometry, we place tight new constraints on the halo virial mass M_vir = 2.2±0.2×10^15 M\odot/h70 (within r ≈ 3 Mpc/h70) and concentration c = 6.2 ± 0.3 when assuming a spherical halo. This agrees broadly with average c(M,z) predictions from recent ΛCDM simulations which span 5 <~ <c> <~ 8. Our most significant systematic uncertainty is halo elongation along the line of sight. To estimate this, we also derive a mass profile based on archival Chandra X-ray observations and find it to be ~35% lower than our lensing-derived profile at r2500 ~ 600 kpc. Agreement can be achieved by a halo elongated with a ~2:1 axis ratio along our line of sight. For this elongated halo model, we find M_vir = 1.7±0.2×10^15 M\odot/h70 and c_vir = 4.6±0.2, placing rough lower limits on these values. The need for halo elongation can be partially obviated by non-thermal pressure support and, perhaps entirely, by systematic errors in the X-ray mass measurements. We estimate the effect of background structures based on MMT/Hectospec spectroscopic redshifts and find these tend to lower Mvir further by ~7% and increase cvir by ~5%.
Gesehen am 21.09.2017